Physical and mental health guidance for a safe re-integration of gymnastics after COVID-19 restrictions from training - Cogan, K.; Darling, B.; Devine, M.; Godfrey, J.; Harris, B.; Casey, E.; Shinohara, M. (2020)
Physical and Mental Health Guidance for a Safe Re-Integration of Gymnastics after COVID-19 Restrictions from Training. USA Gymnastics` Athlete Health and Wellness Council, made up of medical and mental health professionals, program representatives and athlete representatives, has developed the following position statement to serve as a re-integration strategy for return to gymnastics training. The documents contained herein will provide you with important information on why a gradual return to gymnastics is important, how to manage that return for your athletes, as well as other health guidance. This content is specific to physical and mental health aspects associated with a return to gymnastics. You should consult with your coach and doctor to determine the return to gymnastics process that is best for you. This document does not address infectious disease principles involving COVID-19 and the opening of gymnastics facilities. Please reference USA Gymnastics` Member Club Considerations for a Safe Re-opening document for further information regarding COVID-19. The introduction section of this statement provides the "why". We know from sports science research that minimizing injury after a reduction in training requires a gradual return to activity. We also know that every athlete will return to the gym having trained differently while the gym was closed and that this will necessitate an individualized approach to training. The included questionnaire will help guide you through understanding the physical training that each of your athletes sustained while they were away. It will also help you, as the coach, determine where to start with each athlete`s training plan. Also included are training plan templates for all gymnastics disciplines. These will help you determine how to safely progress each athlete through an 8-week plan of gradual training reintroduction. For beginner or compulsory-level athletes, the gradual return to competition may be 4-6 weeks. This plan may be modified for these athletes. Goals are provided for each week of the training plan and recommendations for intensity and volume, as well as discipline-specific training are provided. Additionally, we have included information on the importance of addressing mental health as your athletes return to the gym. Just like each athlete`s physical training was different during the closures, each athlete will return to the gym with unique mental health perspectives. These documents will help coaches honor each athlete`s experience and navigate their return to the gym, from a mental health perspective. Lastly, information is included on nutritional tips and common overuse injuries to be aware of as athletes return to the gym. Despite all of our best efforts, injuries may occur, especially if training is progressed too quickly. Early recognition is pivotal for a safe return. Table of Contents: Introduction -Assessment Tools - Rate of Perceived Exertion (RPE) - Proposed Gymnastics Reintegration Template - USA Gymnastics Post-COVID-19 Reintegration Template - Mental Health - Injury Recognition Facts for Post-COVID-19 Gymnastics Reintegration - Nutrition & Sleep - APPENDIX 1: Pre-Return Fitness Questionnaire APPENDIX 2: USA Acrobatic Gymnastics Post-COVID-19 Reintegration Template APPENDIX 3: USA Men`s Artistic Gymnastics Post-COVID-19 Reintegration Template APPENDIX 4: USA Women`s Artistic Gymnastics Post-COVID-19 Reintegration Template APPENDIX 5: USA Gymnastics Parkour Post-COVID-19 Reintegration Template APPENDIX 6: USA Rhythmic Gymnastics Post-COVID-19 Reintegration Template APPENDIX 7: USA Trampoline & Tumbling Gymnastics Post-COVID-19 Reintegration Template